U-Pb e Lu-Hf em zircão por LA-MC-ICP-MS: metodologia e aplicação no estudo da evolução crustal da porção sudeste do escudo das Guianas - MILHOMEM NETO, João Marinho (Universidade Federal do Pará, 2018)
Combined U-Pb and Lu-Hf in situ analyzes on zircon of magmatic rocks by LA-MC-ICP-MS allow to determine the age and isotopic signature of these rocks, providing valuable information for crustal evolution studies. The application of this systematic, due to its relative simplicity, sensitivity and speed of analysis, is currently one of the most efficient and widely used tools for isotopic and geochronological studies. The southeastern Guiana Shield (GS) is part of the Maroni-Itacaiúnas geotectonic/geochronological Province (MIP) of the Amazonian Craton (AC). The MIP represents an expressive orogenic belt consolidated in the Paleoproterozoic during the Transamazonian orogenic cycle (2.26-1.95 Ga), that includes large segments of Rhyacian juvenile crust and some reworked Archean remnants. It consists mainly of Paleoproterozoic granulitic-migmatitic-gneissic complexes, deformed and metamorphosed metavolcanic and metasedimentary rocks and granitoids (granitic and TTG magmatism). Three tectonic domains are individualized in Brazilian territory of the MIP/GS, called Amapá Block (AB), south-central Amapá and northwest of Pará region, Lourenço Domain (LD), north-central Amapá, and Carecuru Domain (CD), northwest of Pará. The AB is a Neo-Mesoarchean continental block intensely reworked during the Transamazonian Cycle, while the other two domains represent dominantly Rhyacian landmass, with evolution involving stages of subduction of oceanic lithosphere in island and/or continental magmatic arc environments, with relics of reworked Archean continental crust, followed by a colisional stage of tectonic accretion of the magmatic arcs. The objective of this thesis was to implement the experimental procedures of the combined U-Pb and Lu-Hf methodology in zircon by LAMC-ICP-MS at the Pará-Iso/UFPA laboratory and to investigate, in the light of the new U-Pb and Lu-Hf data, the crustal reworking and accretion processes during the Archean and Paleoproterozoic at the southeastern GS. In addition to the AB, some sporadic remnants and inherited Archean zircons have been found in Paleoproterozoic granitoids and raise questions about the involvement and extension of the Archean continental crust in the LD and CD. Whole-rock Sm-Nd data have confirmed the juvenile character of much of MIP. However, for the LD and CD, recurrent Archean Nd-TDM model ages have been identified and also indicate a participation and/or mixing of Neo-Mesoarchean crustal material in the formation of the rocks of these domains. Although several isotopic and geochronological studies have already been carried out in the southeastern GS, the application of combined U-Pb and Lu-Hf analyzes in zircon is still unprecedented. The implantation of Lu-Hf and U-Pb in situ methods in zircon was carried out using a high-resolution Neptune Thermo Finnigan MC-ICP-MS, equipped with a CETAC Nd: YAG 213 nm laser microprobe model LSX-213 G2. ICP-MS and laser instrumentation and operation parameters were established after several analytical sections in order to achieve a satisfactory routine configuration. The results obtained for international reference materials reproduced the literature values with the precision, accuracy and reproducibility necessary for the routine establishment of both U-Pb and Lu-Hf procedures for in situ analyzes of zircons by LA-MC-ICP-MS at the Pará-Iso/UFPA. The description of the experimental protocol and instrumentation for each method, as well as the first results performed on zircon from granitoids/metagranitoids distributed in the three tectonic domains mentioned above were published as two book chapters. Next, isotopic analyzes were performed on zircon of eighteen samples of the AB and LD/CD units. The new U-Pb data consolidated the identification of the main magmatic episodes in the southeasternmost part of the GS. In the AB, two Mesoarchean (~ 3.2 and 2.85 Ga) and one Neoarchean (2.65-2.69 Ga) magmatic events were identified, as well as those in the LD (~ 2.18, 2.14, and 2.12-2.09 Ga) and CD (2.15-2.14 Ga). The Lu-Hf data pointed to the predominance of crustal reworking processes (ƐHf(t) < 0) during the AB and LD/CD formation. The Hf-TDMC model ages ranged from 2.99 to 3.97 Ga for AB and subsidized the identification of two periods of continental crust formation, one in the Eoarchean (~ 4.0 Ga) and the other in the Mesoarchean (3,0- 3.1 Ga). The latter is recognized at a global scale as an important period of crustal accretion. The Eoarchean episode is unprecedent for the southeast of GS and indicates that the crustal growth in the AC started at least 500 Ma earlier than previously suggested (3.51 Ga, whole-rock Nd-TDM). In the Rhyacian domains (LD/CD), the Hf-TDMC model ages were found to be mostly Archean (98.4%). Together with the Nd-Hf isotopic signatures, they indicated the participation of AB crustal material by sediments incorporation in island arc environment in the northwest of the LD, as it has also been recorded in the northwest of Suriname and in the Birimian terrains in Ghana (West African Craton). In the south/southeast of the LD and in the CD assimilation of Archean crust of different ages and proportions in a continental magmatic arc environment may account for the Hf-Nd isotopic signatures and Hf-TDMC model ages of Rhyacian magmatism.